Model Pengembangan Well Being Pada Peserta Didik - Otih Jembarwati (Journal An-Nafs: Kajian Penelitian Psikologi, 2017)
The study was conducted on SMA Gita Bahari Semarang analysis from the results of a series of training programs of devotion that researchers do in SMA Gita Bahari. Research subjects consisted of 30 students of class X, amounting to 20 people per class. From the research results obtained Regression Model as follows: -2A-3,65B + 0,49C + 0,514D = Y, with regression coefficient 0,57, strength prediction model 32,5%. The results show the negative effects of emotional expression and resilience on emotional well-being, while future orientation and teacher type improve emotional well-being. Inferior emotional expression instrumental with low scores as well as cultural factors in interpretation Resilience expression becomes the basis of the regression model. Teacher Type and Future Orientation become important for further development considering its positive impact on emotional well-being. Further ediamonic studies on emotional well-being, training, and application of Teacher Type Understanding, and a more intensive Future Orientation are expected to improve Emotional Wellbeing among learners. More number of Subjects is needed to make the conclusions more generalizable to the wider population.